Vaccination efficacy in patients with chronic lymphocytic leukemia. Issue 1 (2nd January 2023) - Wang, Kevin Y.; Shah, Pratik; Skavla, Brandon; Fayaaz, Fatima; Chi, Jeffrey; Rhodes, Joanna M.
Abstract: Chronic lymphocytic leukemia (CLL) is a disorder of mature malignant B cells with multiple elements of immune dysfunction. Infections are common in CLL patients due to complex immunodeficiency. Vaccines are used as preventative measures for common diseases including influenza, pneumococcus, tetanus/diphtheria and shingles in the general population. Vaccines are utilized to mitigate this risk, although there have been some concerns regarding the efficacy of vaccines in the CLL population due to the inherent complex immune dysfunction associated with the disease. In this review, we describe the clinical and laboratory indicators for efficacy of the vaccines in the CLL population (including COVID-19, influenza, pneumonia, herpes zoster, and tetanus) and discuss immunization recommendations for patients with CLL.